Surface crack growth in a solid cylinder under combined cyclic bending-torsion loading - Chandra, Devi (Asian Research Publishing Network, 2018)
Here, we present fatigue crack growth (FCG) of a surface crack in a solid cylinder under combined cyclic torsionbending load. The effective stress intensity factors were found to be fluctuated during the crack growth. When the loading ratio of the maximum shearing stress over the maximum bending stress was being unity, for a given crack length, the crack aspect ratios between 0.5 and 1 resulted in insignificant differences on the estimated fatigue lives. The effect of the crack depth on the fatigue life was found to be insignificant when the crack position was away from the maximum bending stress location.